The Impact of SFAS No. 2 on Firm Expenditures on Research and Development: Replications and Extensions - Elliott, John; Richardson, Gordon; Dyckman, Thomas; Dukes, Roland (Journal of Accounting Research, 1984)
SFAS No. 2, R&D, Accounting changes, Firm size